Analisis Ketersediaan Fasilitas Kesehatan dan Pemerataan Pelayanan pada Pelaksanaan Jaminan Kesehatan Nasional di Kota Bengkulu, Kebupaten Selumadan Kabupaten Kaur - Yandrizal Yandrizal; Desri Suryani; Betri Anita; Henni Febriawati (Jurnal Kebijakan Kesehatan Indonesia, 2014)
Background: National health insurance is starting in 2014 to gradually move towards Universal Health Coverage. The program should make access health services easier for the community. However limited number of health care givers, a vast population and difficult geographical access mean that there is limited provision of services by the Government and other parties. It appears that the difficulty of access to health facilities remains. The provision of health services is dependent on infrastructure in the community. Without any infrastructure improvements, equitable health service becomes difficult and health coverage for the community is not real. The problem is that whether the national health insurance policy administered by the health-BPJS can improve access to medical services and quality health services to all citizens of Indonesia based on fundamental justice. Objective: To assess the availability and equitable health services as well as the policies for equitable distribution of health facilities within the national health insurance program in the city of Bengkulu, District Seluma and District Kaur. Method: This research is using a formative evaluation method, designed to assess how program policy was implemented and how to modify and to develop new policies so as to bring improvement.The kind of data collected are qualitative and quantitative data. Quantitative data is used to see availability and coverage health, while qualitative data is used to get perception of service provider and program manager of the national health insurance, as well as the challenge and barrier found in implementation process. Data qualitative is obtained using open questionnaire. Quantitative data is derived from a contract between District/municipality health office by health- BPJS and health facility data. Data analysis is compared between District/municipal data, standards according to the regulation and health system according to the WHO and scenario planning. Results: The ratio of the available primary care facilityin Kaur is 17,13 per 100.00o or one per 5.837 inhabitants; while in Bengkulu city it is 13,16 per 100.000 or one for 7.598 inhabitants; and in District Seluma it is one for 7.770 inhabitants. Percentage of contracts for primary services in Bengkulu city is 87,62 %, in District Seluma is 80.41 %, and in District Kaur is 80.73 %. The distance to access primary care facility in District Seluma and District Kaur is 2 hours away if using ‘ojek’ (motorcycle taxi), and the is fare IDR200.000,- (one-way). In Bengkulu, the most distant is 20 minutes and the fare is IDR10.000,-. The ratio of available referral care services in Bengkulu City is 1,88 per 100.000 inhabitants, while in District Seluma is 0,56 per 100.000 inhabitants, and in District Kaur is 0,90 per 100.000 inhabitants. Therefore we need additional primary health facilities supported by the agency of the social security (BPJS), District/City government/Provincial government and the Ministry of Health. While the ratio of beds in the Bengkulu City is 629, in District Seluma is 3.574, and in district Kaur is 2.778. District Seluma needs as many as 129 more beds while District Kaur needs another 60 beds to meet the requirement. The Regional Public hospital in District Kaur and District Seluma are still class D. To increase the capacity at these two hospitals to become class C within 5 (five) years is possible. However, these efforts require special policy from city/district government, Provinces and the Ministry of Health as well as the social security agency (BPJS) considering the limited capacity of the local governments. Conclusion: The availability of primary health facilities in Bengkulu city, Seluma districy and Kaur district are not enough according to Road Map to JKN 2019. Referral health facilities in Seluma district and Kaur district are much lower than the target, whereas in Bengkulu city the number is on target. Utilization of primary health facilities in Bengkulu city, Seluma district and Kaur district are still lower than national average. Utilization of referral helth facilities in the province of Bengkulu is still lower than national average. Latar Belakang: Jaminan Kesehatan Nasional dimulai pada tahun 2014 secara bertahap menuju ke Universal Health Coverage, secara umum yaitu mempermudah masyarakat untuk mengakses pelayanan kesehatan dan mendapatkan pelayanan kesehatan yang bermutu. Pemberi pelayanan kesehatan yang terbatas, penyebaran penduduk yang luas dan akses yang terbatas, menyebabkan kurang supply (penyediaan layanan) oleh pemerintah dan pihak lain, sehingga akan muncul kesulitan terhadap akses ke fasilitas kesehatan. Penyediaan pelayanan kesehatan tergantung pada infrastruktur di masyarakat, tanpa ada perbaikan infrastruktur pemerataan pelayanan kesehatan menjadi sulit dan jaminan kesehatan bagi masyarakat merupakan hal yang tidak riil. Permasalahan yang muncul apakah kebijakan Jaminan Kesehatan Nasional oleh BPJS Kesehatan ini dapat meningkatkan akses pelayanan kesehatan dan pelayanan kesehatan yang bermutu kepada seluruh warga Indonesia dengan asas keadilan. Tujuan: Mengetahui ketersediaan dan pemerataan pelayanan kesehatan serta upaya kebijakan pemerataan fasilitas kesehatan pada program Jaminan Kesehatan Nasional di Kota Bengkulu, Kabupaten Seluma dan Kabupaten Kaur. Metode: Penelitian ini menggunakan rancangan metode analisis evaluasi formatif yang dirancang untuk menilai bagaimana program/kebijakan sedang diimplementasikan dan bagaimana pemikiran untuk memodifikasi serta mengembangkan sehingga membawa perbaikan. Jenis data yang dikumpulkan kuantitatif dan kualitatif. Data kuantitatif digunakan untuk melihat ketersediaan dan cakupan layanan kesehatan, sedangkan data kualitatif untuk mendapatkan persepsi dari penyedia layanan dan manajer program terhadap Jaminan Kesehatan Nasional serta tantangan dan hambatan yang ditemukan pada proses implementasinya. Data Kualitatif diperoleh dengan mengunakan kuesioner terbuka, data kuantitatif berasal dari Kontrak Dinas Kesehatan Kaupaten/kota dengan BPJS dan data fasilitas kesehatan. Analisis data dibandingkan antar kabupaten/kota, standar yang ditetapkan berdasarkan peraturan, sistem kesehatan menurut WHO dan perencanaan berdasar skenario (scenario planning) Hasil: Rasio ketersediaan fasilitas pelayaan primer di Kabupaten Kaur 17,13 per 100.000 atau satu banding 5.837 penduduk, sedangkan di Kota Bengkulu lebih kecil 13,16 per 100.000 ribu atau satu banding 7.598 penduduk dan Kabupaten Seluma satu banding 7.770 penduduk. Persentase nilai kontrak untuk pelayanan primer di Puskesmas Kota Bengkulu sebesar 87,62%, Kabupaten Seluma sebesar 80.41%, Kabupaten Kaur sebesar 80.73% Jarak tempuh ke pelayanan primer di Kabu- paten Seluma dan Kabupaten Kaur paling jauh kira 2 jam perjalanan dengan mengunakan Ojek dan ongkos sekali jalan Rp. 200.000,- dibandingkan Kota Bengkulu paling jauh 20 menit dengan ongkos ojek Rp. 10.000,-, Rasio ketersediaan fasilitas pelayaan rujukan di Kota Bengkulu 1,88 per 100.000, Kabupa- ten Seluma 0,56 per 100.000 dan Kabupaten Kaur 0,90 per 100.000 penduduk, sehingga perlu penambahan fasilitas kese- hatan tingkat pertama oleh Badan Penyelenggaran Jaminan Sosial, Pemerintah kabupaten/kota/provinsi dan Kementerian Kesehatan. Sedangkan Rasio tempat tidur untuk Kota Bengkulu 629, Kabupaten Seluma 3574 dan Kabupaten Kaur 2778. Kebutuhan Kabupaten Seluma sebanyak 129 Tempat Tidur dan Kabupaten Kaur sebanyak 60 Tempat Tidur untuk memenuhi target, Rumah Sakit Umum Daerah Kabupaten seluma dan Kabu- paten Kaur masih kelas D. Peningkatan kelas rumah sakit men- jadi kelas C dalam kurun waktu 5(lima) tahun kedepan sangat memungkinkan, upaya ini memerlukan kebijakan khusus dari Pemerintah Daerah Kabupaten, Provinsi dan BPJS serta Kemen- terian Kesehatan mengingat keterbatasan pemerintah daerah. Kesimpulan: Ketersediaan fasilitas kesehatan tingkat pertama saat ini di Kota Bengkulu, Kabupaten Seluma dan Kabupaten Kaur belum mencukupi target yang ingikan menurut Peta Jalan Menuju JKN 2019. Fasilitas kesehatan rujukan di Kabupaten Seluma dan Kabupaten Kaur masih rendah dibandingkan tar- get, sedangkan Kota Bengkulu telah mencapai target. Pemanfaatan fasilitas kesehatan tingkat pertama di Kota Bengkulu, Kabupaten Seluma dan Kabupaten Kaur masih rendah dari Provinsi Daerah istimewa Yogjakarta. Pemanfaat fasilitas kesehatan rujukan di Provisinsi Bengkulu masih rendah dari pada dari Provinsi Daerah istimewa Yogjakarta.